Investigating magnetism - Walker, Sally M. (Minneapolis : Lerner Publications, 2012)
An introduction to magnetism that explains what it is, what materials are magnetic, how magnets work, what magnetic poles are, and what the different types of magnets are.
Magnets -- Magnetic materials -- How magnets work -- Magnetic poles -- Kinds of magnets.
Includes bibliographical references (p. 39) and index.
Science and Children (N.S.T.A.)
Science and Children (N.S.T.A.), October 2011
4.0
3-6
3-6
Keywords: Magnetism -- Juvenile literature; Magnetism -- Experiments -- Juvenile literature; Magnets -- Juvenile literature; Magnetism; Magnetism -- Experiments; Magnets; Magnetism; Magnetism -- Experiments; Magnets